New Strains of Bacteria that Degrade Aromatic Compounds Act as Antagonists of Highly Active Phytopathogens - Tatiana O. Anokhina; Tatiana Z. Esikova; Tatiana N. Abashina; Nataliya E. Suzina; Inna P. Solyanikova (Proceedings, 2020)
The intensive development of agriculture leads to the depletion of land and a decrease in crop yields and in plant resistance to diseases. A large number of fertilizers and pesticides are currently used to solve these problems. Chemicals can enter the soil and penetrate into the groundwater and agricultural plants. Therefore, the primary task is to intensify agricultural production without causing additional damage to the environment. This problem can be partially solved using microorganisms with target properties. Microorganisms that combine several useful traits are especially valuable. The aim of this work was to search for new microbial strains that possess a complex, technologically significant potential, such as increasing the bioavailability of nutrients, phytostimulation, antifungal effect and degradation of pesticide residues and other xenobiotics. Few isolated Bacillus and Pseudomonas strains were characterized by high activity against fungal phytopathogens. One of the bacterial strains identified as Bacillus sp. on the basis of the 16S rRNA gene sequence was characterized by an unusual cellular morphology and development cycle, significantly different from all previously described bacteria of this genus. All isolated bacteria are capable of benzoate degradation, as a sign of the ability to degrade aromatic compounds. Isolated strains were shown to be perspective agents in biotechnologies.